"Nós, professoras-mediadoras": Os efeitos da parceria escola-universidade na mediação da leitura literária - Santos, Stéfane de Almeida dos (2024)
From the secular socio-historical course, in which the school is the prelude to the production of books aimed at children, Literature and Education are sides of the same coin: literary education. Equally, under the aegis of the formation of readers together with their literary literacy, the school environment becomes one of the institutions with the greatest circulation of children's literature, conferring on it the burdens and bonuses of being a privileged space. From this privilege comes the responsibility for reading mediation, in such a way that, organically, it is the teacher who takes it on. From this perspective, we have taken as a premise the relevance of a partnership with the university, especially in terms of academic extension, as a strategy to involve readers and mediators in this process. This dissertation aims to investigate the effects of the partnership between school and university in the mediation of literary reading carried out by a group of teachers from the Teacher Lúcia Giovanna Duarte de Melo Municipal School, at João Pessoa/PB, based on the actions developed, from 2020 to 2022, by the extension project entitled Cultura literária na escola: para ler, ouvir, ver e sentir, associated to the Federal University of Paraíba (UFPB). Concerning the methodology, this research is of an applied nature, whose character is both exploratory and explanatory, as it aims to bring to light ‘what’ the effects are, ‘how’ they are revealed and ‘why’ they are relevant, with arguments supported by the writings of Cerrillo (2002; 2007), Colomer (2002; 2007; 2017), Imbernón (2010), Munita (2014), and others. Nonetheless, this is an investigation aligned with the qualitative approach, whose procedures combine case study, action research and participant research, as well as the data collection technique of observing the academic-school context and conducting individual interviews and focus groups. The subjects, then, constitute a group of 10 (ten) teachers from the aforementioned school, who have been involved throughout the three-year partnership. As a result of the research process, we have identified three macro effects, which are made up of layers and nuances that unite knowledge and actions: 1) Building a community of readers made up of subjects from basic and higher education, including the collective development of a permanent school reading project that places literature in a privileged place in both the curriculum and pedagogical practice; 2) Bringing school and university closer together through the production of knowledge and scientific work (books, chapters, dissertations and monographs) thanks to the union between teaching and academic research; and 3) Reverberation of the partnership in reading mediation from the socio-cultural, aesthetic and professional dimensions.